Revitalizing Balinese Dance for Generation Z: Critical Ethnography to Overcome the Socio-Cultural Identity Crisis - I Wayan Gede Lamopia; Riza Wulandari; Ni Wayan Setiasih (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Globalization and the development of digital technology have changed the patterns of interaction and cultural expression among the younger generation, especially Generation Z (Gen Z). In Bali, this phenomenon has given rise to a major challenge in the form of a socio-cultural identity crisis, characterized by Gen Z's alienation from their local culture and a loss of value orientation, which can lead to a weakening of social cohesion and national identity. This study aims to identify the forms of socio-cultural identity crisis faced by Gen Z and formulate the reinvention of Balinese dance as a contextual mitigation strategy. The study uses qualitative methods with an ethnographic approach through observation, in-depth interviews, and document studies. The results of the study map three main sub-topics of identity crisis, including (1) a shift in values, in the form of a dominant pragmatic and consumptive orientation towards art; (2) a crisis of collective representation, when Balinese dance is no longer perceived as a medium of self-expression for Gen Z; and (3) the influence of digital lifestyle, which shifts the practice of learning and appreciating art to an instant virtual space. The object of this research is Widya Prakrti Dance. The research is expected to support arts education, strengthen cultural literacy, and expand the space for appreciating Balinese dance through digital media, creative learning platforms, and curricular and co-curricular activities for the younger generation who are oriented towards collaboration across contemporary local communities.